Pharmacokinetics of ciprofloxacin in layer chicks - AI – Khafaji, B. S.; Al-Khayyat, A. A.; Al-Shaha, O.M.S. (The Iraqi Journal of Veterinary Medicine, 1999)
Pharmacokinetics parameters of ciprofloxacin were calculated from constructed plasma disappearing curves (PDC) after oral or i.v. injection of 5mg / kg in two-week old hybird layer · The i.v. PDC indicated a first order biphasic kinetic. The distribution phase was too short to be considered. The parameters of the elimination phase phase indicated that the biological half – life ( t 12) was 3.7 hours and the volume of distribution (Vd) was 1.7 1/kg. The oral PDC indicated a first order kinetic with a peak plasma level (PPL) of 3.0 ug/ml achieved after 1.75 hours , a t 12 of 2.9 hours and a Vd of 1.7 1/kg . Bioavailability value was 84 +9.7% . Binding of ciprofloxacin to chicken plasma protein was estimated to be 25.4 61.3%.